Using Ansys Fluent to Study Flow Characteristics and Heat Transfer Enhancement by Inserting Different Sizes of Dimple in Three-Dimensional Horizontal Single Pipe Heat Exchanger - Sarmad Ahmed Ali (Journal of Advanced Industrial Technology and Application, 2025)
In many engineering applications, the relevance of heat transfer improvement has grown, and a lot of work has gone into using various ways to enhance the hydraulic thermal performance of fluids running through pipes. This study uses numerical analysis to examine the thermal performance of turbulent flow properties and heat transfer under a uniform 30000 W/m2 heat flux in dimpled pipes. For several designs of dimpled pipes, the friction factor, heat transfer rate, and performance assessment criterion were calculated and compared with smooth pipes. The examples under consideration are within the range of 8000 to 14,000 Reynolds numbers. For this, the ANSYS Fluent 2023 R2 is employed. The governing flow equations are modeled using the Reynolds-averaged Navier-Stokes equations (RANS). To simulate turbulent flow next to the inner wall surface, the realizable k-? turbulence model is applied with increased wall conditions. The results of the current study showed the presence of dimples on the surface of the pipe significantly enhances the rate of heat transfer represented by the Nusselt number compared to the normal smooth pipe. Also, the analyzed models indicated by the results of the numerical investigation have high average Nusselt counts, low pressure, overall performance criterion, and low average thermal resistance due to the increase in the Reynolds number. The dimpled pipe with different radii (2,3, and 4 mm) has an increased percentage of enhanced heat transfer (79.91, 86.77, and 94.47%) compared to the smooth pipe.